2018
DOI: 10.1002/mp.12760
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of range‐based registration using daily cone beam CT for intensity‐modulated proton therapy

Abstract: Range-based registration can efficiently mitigate range deviation due to patient positioning and anatomical changes. It can shorten patient positioning time and reduce the patient's dose from CBCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…34 Moreover, the type and energy of therapeutic radiation and the radiation delivery technique affect the required HU accuracy. 35 Based on our review of the literature, it appears the general strategy is to improve CBCT HU accuracy as close as possible to HU accuracy in helical CT to minimize errors in dose calculations. [36][37][38] In our work, 2D ASG combined with the GSS method provided better HU accuracy than the standard clinical CBCT protocol (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Moreover, the type and energy of therapeutic radiation and the radiation delivery technique affect the required HU accuracy. 35 Based on our review of the literature, it appears the general strategy is to improve CBCT HU accuracy as close as possible to HU accuracy in helical CT to minimize errors in dose calculations. [36][37][38] In our work, 2D ASG combined with the GSS method provided better HU accuracy than the standard clinical CBCT protocol (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is challenging to define a target HU accuracy for CBCT‐based dose calculations; dose calculation errors depend on the cumulative effect of HU inaccuracy along the path of the therapeutic radiation, which is a function of multiple factors, such as location in the patient, tissue composition, patient size, and motion artifacts 34 . Moreover, the type and energy of therapeutic radiation and the radiation delivery technique affect the required HU accuracy 35 . Based on our review of the literature, it appears the general strategy is to improve CBCT HU accuracy as close as possible to HU accuracy in helical CT to minimize errors in dose calculations 36–38 .…”
Section: Discussionmentioning
confidence: 99%
“…Without scatter correction,one phantom study showed that the error of change of the calculated water-equivalent thickness (WET; the surrogate of proton range from daily CBCTs) was within 2 mm per 1 cm of phantom size change. 10 Proton range estimated by CBCT has been used in proton dose calculation 9,14 and proton range-based registration 10 but not in QACT frequency reduction.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is the use of proton range change in the CBCT from day 1, because we are more interested in the relative change of the range instead of the exact range itself. Without scatter correction, one phantom study showed that the error of change of the calculated water‐equivalent thickness (WET; the surrogate of proton range from daily CBCTs) was within 2 mm per 1 cm of phantom size change 10 . Proton range estimated by CBCT has been used in proton dose calculation 9,14 and proton range–based registration 10 but not in QACT frequency reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation